2021
DOI: 10.3390/coatings11111288
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Wear-Resistant Coating on Ti6Al4V Alloy by Cold Spraying and Plasma Electrolytic Oxidation

Abstract: In order to improve the wear resistance of Ti6Al4V alloy, the alloy was first coated with alumina-reinforced aluminum coating (CS-coating) by cold spraying, and then the alloy with CS-coating was processed by plasma electrolytic oxidation (PEO) under unipolar mode and soft sparking mode, respectively, to prepare wear-resistant PEO coatings. For comparison, Ti6Al4V alloy without CS-coating was also subjected to PEO treatment. The microstructure, phase composition, hardness, and wear resistance of the PEO coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It has been reported that the soft sparking technique causes the formation of compact PEO film with good wear performance, and the soft sparking mode is achieved under low voltage conditions. 55,56 Because the voltage decreased with increasing concentration (Fig. 6), the soft sparking mode may occur at higher concentrations.…”
Section: Resultsmentioning
confidence: 98%
“…It has been reported that the soft sparking technique causes the formation of compact PEO film with good wear performance, and the soft sparking mode is achieved under low voltage conditions. 55,56 Because the voltage decreased with increasing concentration (Fig. 6), the soft sparking mode may occur at higher concentrations.…”
Section: Resultsmentioning
confidence: 98%
“…The Ti6Al4V alloy, due to its low density, high specific strength, and excellent performance, is one of the mainstream materials used for making aero-engine blades [1][2][3][4][5]. In an aero engine, the clearance between the blade case is a key factor that affects its efficiency [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion, wear, and fatigue attacks are common problems for many engineering materials used in industrial settings, which cause the material's surface to deteriorate quickly. Hard coatings are applied to materials in order to save expenses, save energy, and preserve raw materials because of these factors [2]. Surface improvement of engineering materials can be used to avoid and control degradation and service failure in industries.…”
Section: Introductionmentioning
confidence: 99%